Relationship between Knowledge Level and Dietary Adherence in Patients with Type II Diabetes Mellitus at Pajang Health Center Surakarta - Sheli Duwita Sari; Abi Muhlisin (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Deficiency in glucose metabolism due to absolute or relative insulin deficiency leads to increased blood sugar levels beyond the established normal range; this condition is characterized by a collection of symptoms called diabetes mellitus. Dietary adherence in individuals with type II diabetes mellitus can be seen from their level of knowledge. The research aims to determine the relationship between the level of knowledge and dietary compliance in people with type II diabetes mellitus. This research is a quantitative research with a cross-sectional approach. This research was conducted in the Pajang Surakarta Community Health Center area on all Type II Diabetes Mellitus sufferers and was carried out in November 2023. The research population was all Diabetes Mellitus patients at the Pajang Surakarta Community Health Center, as many as 148 people. The research sampling technique was Consecutive Sampling, so the sample obtained was 60. Data was collected using questionnaires and interviews. Analysis of research data with bivariate analysis using the Chi-Square test. The research results show a real relationship between the knowledge level and diet adherence with a p-value = 0.040. The level of knowledge about Diabetes can influence adherence to a diabetes diet because patients need good knowledge regarding recognizing the signs and symptoms of DM, the risk of complications occurring, and care in treating Diabetes. Therefore, the role of health workers is needed to hold outreach activities to provide knowledge about diabetes mellitus, starting from the definition, signs and symptoms, risk factors, prevention methods and complications that occur by providing regular and scheduled counselling. Keywords: Dietary Adherence, Diabetes Mellitus, Knowledge